Defining Success in Lung Transplantation: From Survival to Quality of Life - Kolaitis, Nicholas A.; Singer, Jonathan P. (Seminars in Respiratory and Critical Care Medicine, 2018)
Lung transplantation (LT) has the potential to extend survival and improve quality of life (QOL) for patients suffering from end-stage lung disease. This review describes the many ways in which success can be defined in LT. It evaluates the improvements in survival outcomes after LT over time, and describes ways to measure the success of LT other than survival after transplantation. It also addresses the importance of patient-centered outcomes and how improvements in health-related quality of life (HRQL) are pivotal to defining success within LT.
Keywords: lung transplantation; success; survival; quality of life; health-related quality of life; HRQL